(untitled) (Itinera, 2020)
The essay focuses on the theme of natural teratology, or the study of deformities, and above all on the positive figure of the freak, which I am going to analyze from a social and spectacular point of view. The analysis will go on probing the territories of the bizarre and the marvelous as presented by the Great American Museum of Barnum.